TEACHING ENGLISH TO ADULT STUDENTS AT MANAGEMENT RESEARCH AND EDUCATION (LP2M) EL-RAHMA EDUCATION CENTER PALEMBANG - ariya agustin (Journal of English Education, Literature and Linguistics, 2019)
The Objectives of the study are to describe the system used in Teaching English as a foreign language at LP2M El-Rahma Education Center Palembang, whether or not it is relevant with the principles of the procedure for the development of instructional system and to find out whether the system is suitable to the adult student’s needs or not. A descriptive method was used in this research, becauase the writer described the data as they are. The subject of the study is the population of the second semester students of LP2M El-Rahma Education Center Palembang in the academic year 2006/2007, there are 180 students from the population 40 students are taken as the sample randomly. The data are obtained through documentation, interview to the English instructors who taught at LP2M El-Rahma Education Center Palembang . Observation and Questionaire given to the students. The data are analyzed by means of percentage . Based on the results of the data analysis, the writer found that the system used in TEFL at LP2M El- Rahma Education Center Palembang was relevannt to the system of teaching and the system applied was not suitable to the students’ needs. they needed to learn English computer science in the term of writing grammatically, speaking with public either science textbooks espeacially which are written in English.